PENGENALAN DAN SOSIALISASI PENGARUH POSITIF DAN NEGATIF SMARTPHONE BAGI REMAJA KARANGTARUNA SEBAGAI MEDIA EDUKASI DALAM PERKEMBANGAN TEKNOLOGI INFORMASI - Dede Supiyan; Rahmawati; Nasrul Hidayah (Abdi Jurnal Publikasi, 2025)
Smartphone use has become a global phenomenon that has a major impact on people's lives, including teenagers. On the one hand, smartphones provide significant benefits, such as easy access to information, global communication and opportunities for self-development. However, on the other hand, smartphone misuse can cause various problems, such as addiction, decreased quality of social interactions, and exposure to negative content. This research aims to introduce and socialize the positive and negative influences of smartphones to Karang Taruna youth, as an educational medium that is relevant to the development of information technology. This activity is carried out through a participatory approach involving introductory sessions, group discussions, case simulations, and comprehensive evaluations. Data was collected using pre- and post-activity survey methods to measure participants' level of understanding. The results showed that 85% of participants experienced increased understanding of digital literacy, cyber security and time management using smartphones. This activity also encourages participants' critical awareness to use smartphones wisely and productively, in line with Karang Taruna's educational values. This research concludes that introducing and socializing the influence of smartphones through an educational approach can be an effective strategy in shaping positive attitudes and behavior of teenagers in the digital era. Therefore, it is recommended to develop sustainable programs that involve stakeholders, such as educators, parents and youth communities, to support ethical and innovative digital literacy..